Autotaxin and Lysophosphatidic Acid Signalling: the Pleiotropic Regulatory Network in Cancer - Vít, Ondřej; Petrák, Jiří (Folia biologica, 2023)
Autotaxin, also known as ecto-nucleotide pyrophosphatase/phosphodiesterase family member 2, is a secreted glycoprotein that plays multiple roles in human physiology and cancer pathology. This protein, by converting lysophosphatidylcholine into lysophosphatidic acid, initiates a complex signalling cascade with significant biological implications. The article outlines the autotaxin gene and protein structure, expression regulation and physiological functions, but focuses mainly on the role of autotaxin in cancer development and progression. Autotaxin and lysophosphatidic acid signalling influence several aspects of cancer, including cell proliferation, migration, metastasis, therapy resistance, and interactions with the immune system. The potential of autotaxin as a diagnostic biomarker and promising drug target is also examined.
Keywords: Lysophospholipids; Neoplasms; nádory; cancer; Signal Transduction; fosfodiesterasy; lysophosphatidic acid; lidé; lysofosfolipidy; LPA; autotaxin; signal transduction; signální transdukce; ENPP2; Phosphoric Diester Hydrolases; Humans